2014
DOI: 10.1016/j.vetimm.2014.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Canine lymphoma as a comparative model for human non-Hodgkin lymphoma: recent progress and applications

Abstract: The term “lymphoma” describes a heterogeneous group of disorders involving monoclonal proliferation of malignant lymphocytes. As a group, lymphomas are among the most common tumors of dogs. Yet our enumeration and understanding of the many subtypes of lymphoma have been relatively slow, perhaps in part because for many years lymphoma was treated as a singular entity rather than a group of distinct diseases. The recognition that the full spectrum of lymphoid malignancies seen in humans also occurs in dogs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
134
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 61 publications
2
134
0
4
Order By: Relevance
“…These results correlate with a clinical investigation showing poorer prognosis in the case of high-grade T-cell canine lymphoma (6), and with the results of similar studies involving the use of established canine lymphoma and leukaemia cell lines (15). The use of drugs with proven in vitro activity against specific tumour cells may be useful in solving this problem.…”
Section: Discussionsupporting
confidence: 88%
“…These results correlate with a clinical investigation showing poorer prognosis in the case of high-grade T-cell canine lymphoma (6), and with the results of similar studies involving the use of established canine lymphoma and leukaemia cell lines (15). The use of drugs with proven in vitro activity against specific tumour cells may be useful in solving this problem.…”
Section: Discussionsupporting
confidence: 88%
“…Extensive evidence suggests canine NHL to be a model for human NHL. Following the separation of canine lymphoma cells, the study by Ito et al (8) cultured and passaged them and developed a xenograft model. Subsequently, their molecular profile was examined and it was concluded that not only is canine NHL morphologically and behaviorally similar to human NHL, but its molecular changes also mimic human lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, invasion and metastasis can be followed in this model. Thirdly, with regard to the fact that dogs live alongside humans, they are exposed to the same risk factors and so the course of molecular changes and genetic mutations can also be studied (4,8,15).…”
Section: Discussionmentioning
confidence: 99%
“…These LPCs had phenotypic properties consistent with tumor-initiating or tumor-propagating cells (TIC/TPC); they also persisted in the xenotransplantation setting, suggesting that they were relevant to the biology of this disease in vivo 6 . When compared with the bulk of the tumor cells, LPCs showed significantly lower expression of 44 genes across the genome, mapping to cell cycle and transmembrane signaling pathways 7 . This indicated that LPCs exhibit the characteristic “slow proliferation” seen in normal bone marrow-derived hematopoietic stem cells and in TIC/TPC in other cancers.…”
Section: Introductionmentioning
confidence: 99%